2000
DOI: 10.1096/fj.00-0502fje
|View full text |Cite
|
Sign up to set email alerts
|

Triiodothyronine‐mediated upregulation of UCP2 and UCP3 mRNA expression in human skeletal muscle without coordinated induction of mitochondrial respiratory chain genes

Abstract: Triiodothyronine (T3) increases mitochondrial respiration and promotes the uncoupling between oxygen consumption and ATP synthesis. T3 effect is mediated partly through transcriptional control of genes encoding mitochondrial proteins. We determined the effect of T3 on mRNA levels of uncoupling proteins (UCP) and proteins involved in the biogenesis of the respiratory chain in human skeletal muscle and on UCP2 mRNA expression in adipose tissue. Ten young, healthy males received 75 to 100 5g of T3 per day for 14 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
57
0
5

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(69 citation statements)
references
References 52 publications
7
57
0
5
Order By: Relevance
“…type IIB≥type IIA/IIX>type I, in transgenic mice was similar to the endogenous profile described in human skeletal muscle [4]. Moreover, regulation by thyroid hormone and fasting was observed as shown earlier in humans [13,17]. Therefore, all regulatory sequences crucial for tissue and fibre type distribution, as well as for hormonal and nutritional regulation were present in the 16 kb transgene.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…type IIB≥type IIA/IIX>type I, in transgenic mice was similar to the endogenous profile described in human skeletal muscle [4]. Moreover, regulation by thyroid hormone and fasting was observed as shown earlier in humans [13,17]. Therefore, all regulatory sequences crucial for tissue and fibre type distribution, as well as for hormonal and nutritional regulation were present in the 16 kb transgene.…”
Section: Discussionsupporting
confidence: 81%
“…Fatty acids are potential mediators of this effect, which may at least in part depend on the activation of peroxisome proliferator-activated receptor (PPAR)α in skeletal muscle [15]. Thyroid hormones are also strong inducers of UCP3 expression in humans and in mice [14,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…The overexpression of UCP3 is much lower than that of most of the previous models both in terms of mRNA (66-and 18-fold induction) and protein (25-and 15-fold induction) [27,28]. Moreover, the range of expression in h-UCP3 mice is compatible with the inductions observed in vivo in humans during fasting and thyroid hormone or etomoxir treatments [19][20][21]. A recent study reported data with a twofold overexpression of UCP3 in hindlimb muscle of C57Bl/6 mice [29,30].…”
Section: Discussionmentioning
confidence: 72%
“…This strategy ensured moderate UCP3 overproduction specifically targeting type II skeletal muscles. Therefore, the UCP3 distribution seen in human tissues and the physiological range of variations observed in clinical studies were respected [5,[19][20][21]. Mitochondrial uncoupling was investigated on permeabilised muscle fibres.…”
Section: Introductionmentioning
confidence: 99%
“…30 Thyroid hormone treatment, known to increase metabolic rate, induces UCP3 mRNA expression in humans. 31 Further evidence for a role of UCP3 in energy metabolism comes from transgenic mice models. Mice overexpressing UCP3 in skeletal muscle have been generated and these mice are lean despite an increased energy intake compared to controls.…”
Section: Discussionmentioning
confidence: 99%